GEREJA YANG DIMUSUHI SATAN (THE CHURCHES ATTEMPTED TO SATAN): ANALISA DAN PENAFSIRAN WAHYU 12:1-17 (ANALYSIS AND INTERPRETATION OF REVELATION 12: 1-17) - Lintuuran, Wempie Jules (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2019)
Revelation 12: 1-17 is located at the center of the Book of Revelation in its structural structure. This means that this part is important. This chapter reveals the great contradiction between good and evil, between the Lord Jesus Christ and His hostile Satan and his evil agents. This article analyzes this important vision of the Apostle John, then interprets it from the perspective of historicalism. Satan's hostility towards the Lord Jesus Christ, which began in Heaven and continued on earth, the victory of the Lord Jesus Christ who defeated Satan, the persecution and heresy by Satan and his agents towards the Church that is faithful to God from time to time to the end of time, is described in the article this. Wahyu 12:1-17 terletak di bagian pusat Kitab Wahyu dalam struktur khiastiknya. Hal ini mengartikan bahwa bagian ini penting. Pasal ini mengungkapkan pertentangan besar antara yang baik dan jahat, antara Tuhan Yesus Kristus dan Jemaat-Nya yang dimusuhi Satan dan agen-agen kejahatannya. Artikel ini menganalisa penglihatan Rasul Yohanes yang penting ini, kemudian menafsirkannya dari perspektif historisisme. Permusuhan Satan terhadap Tuhan Yesus Kristus yang dimulaikan di Sorga dan dilanjutkan di bumi, kemenangan Tuhan Yesus Kristus yang mengalahkan Satan, persekusi dan penyesatan oleh Satan dan agen-agennya terhadap Jemaat yang setia kepada Tuhan dari masa ke masa sampai ke akhir zaman, diuraikan dalam artikel ini.